Effects of Low-Level Laser Therapy on Osseous Defects Distal to Mandibular Second Molar after Extraction of Impacted Third Molar - Ling-Yu Li; Jie Chen; Ming Yu; Yue-Ling Li; Gang Zhou (Applied Bionics and Biomechanics)
Objective. To evaluate the efficiency of low-level laser therapy on the distal osseous defects of the mandibular second molar (M2) after the adjacent impacted third molar (M3) extraction. Methods. A total of 59 clinic cases were screened out, whose M3 were impacted and the distal alveolar bone of M2 had been destroyed horizontally. They were randomly divided into 2 groups based on whether they would have laser irradiation or not after M3 extraction. Then, postoperative complications of the 2 groups were compared. The alveolar bone level distal to M2 was established before and 3 to 6 months after M3 extraction by radiographic evaluation, which was compared between two groups. Results. The incidence of severe pain and mouth-opening limitation was significantly lower in the LLLT group than that in the control group. The amount of bone formation in the LLLT group was higher than that in the control group 3 months after the operation, and the difference was statistically significant. But the difference was not statistically significant 6 months after surgery. Conclusion. LLLT may alleviate postoperative complications and improve early osteogenesis. It is a viable option for use in the treatment of osseous defects distal to mandibular second molars following extraction of impacted third molars.